Pengembangan Modul Pembelajaran Berbasis Proyek pada Mata Pelajaran Simulasi dan Komunikasi Digital SMK - Zekri Zekri; Ganefri Ganefri; Muhammad Anwar (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
This study aims to produce a reasonable digital simulation and communication module to improve the communication and collaboration skills of vocational students. This research is an R&D research with the 4D model, Subject The research is 30 students of SMK N 7 Padang. The instruments used in this research consisted of validation form of digital simulation and communication module, student’s response questionnaire form, form of the learning process with a project-based learning model, self-assessment of collaboration skill, peer-assessment of collaboration skill, observation sheet of collaboration skills, and observation sheet of communication skill. The data were analyzed using qualitative and quantitative analysis. Qualitative analysis for data of module validation and student's response. Quantitative analysis for collaboration skill training of self-assessment; peer-assessment; and observation sheet data and communication skill training of observation sheet data that for both of them by percentage calculation; gain score calculation; U Mann Whitney, and for the percentage of the learning process. The result showed that the module that has produced was reasonable to improve communication and collaboration skill of vocational students, where students communication skill training have moderate categories, it is 47,96% from “less” to be “good” with the significant difference before and after using the module score, by signification value (Sig.) was 0,000, student’s collaboration skill training have moderate categories, it is 31,54% from “enough” to be “good” with the significant difference before and after using the worksheet score, by signification value (Sig.) was 0,000 and the module got the student’s response with very well categories (A).